Efficacy and Safety of Intravitreal Aflibercept for Polypoidal Choroidal Vasculopathy in the PLANET Study: A Randomized Clinical Trial - Lee, Won Ki (JAMA Ophthalmol, 2018)
IMPORTANCE: Polypoidal choroidal vasculopathy (PCV) is common in Asian populations, but an optimal treatment approach remains to be confirmed. OBJECTIVE: To evaluate intravitreal aflibercept injection (IAI) in participants with PCV and compare IAI monotherapy with IAI plus rescue photodynamic therapy (PDT). DESIGN, SETTING, AND PARTICIPANTS: This 96-week, double-masked, sham-controlled phase 3b/4 randomized clinical trial was conducted at multiple centers in Australia, Germany, Hong Kong, Hungary, Japan, Singapore, South Korea, and Taiwan from May 2014 to August 2016, and included adults 50 years or older with symptomatic macular PCV and a best-corrected visual acuity of 73 to 24 Early Treatment Diabetic Retinopathy Study letters (20/40-20/320 Snellen equivalent). INTERVENTIONS: Participants received 2 mg of IAI at weeks 0, 4, and 8. At week 12, participants with a suboptimal response were randomized 1:1 to receive IAI plus sham PDT (IAI monotherapy) or a “rescue” of IAI plus rescue PDT (IAI/PDT). Participants who did not qualify for rescue received IAI every 8 weeks; those qualifying for rescue received IAI every 4 weeks plus sham/active PDT. When the rescue criteria were no longer met, injection intervals were gradually extended to 8 weeks. MAIN OUTCOMES AND MEASURES: Noninferiority of IAI monotherapy to IAI/PDT for mean change in best-corrected visual acuity from baseline to week 52 (95% CI of the difference entirely above −5 letters). RESULTS: Of the 318 participants, the mean (SD) age was 70.6 (8.2) years, 96 (30.2%) were women, and 152 (47.8%) were Japanese. Monotherapy with IAI was noninferior to IAI/PDT for the primary end point (+10.7 vs +10.8 letters, respectively; 95% CI, −2.9 to 1.6; P = .55), with few participants requiring rescue therapy (19 [12.1%] vs 23 [14.3%], respectively). Participants in both treatment groups had similar reductions in central subfield thickness from baseline to week 52 (−137.7 [IAI monotherapy] vs −143.5 μm [IAI/PDT]). At week 52, 49 (38.9%) and 60 participants (44.8%) had no polypoidal lesions observed on indocyanine green angiography in the IAI monotherapy and IAI/PDT groups, respectively. Furthermore, 116 (81.7%) and 136 (88.9%), respectively, had no polypoidal lesions with leakage. The most frequent ocular adverse events were conjunctival hemorrhage (IAI monotherapy, 8 [5.1%]) and dry eye (IAI/PDT, 9 [5.6%]). CONCLUSIONS AND RELEVANCE: Improvement in visual and/or functional outcomes was achieved in more than 85% of participants who were treated with IAI monotherapy, with no signs of leakage from polypoidal lesions in more than 80%. As fewer than 15% met the criteria of a suboptimal response to receive PDT, the potential benefit of adding PDT cannot be determined. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT02120950